2012
DOI: 10.1002/ceat.201200339
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Catalyst Loading and Body Effects on a Gas‐Liquid Trickle‐Flow Bed

Abstract: The influence of tortuosity and fluid volume fractions on trickle-flow bed performance was analyzed. Hydrodynamics of the gas-liquid downward flow through trickle beds, filled with industrial trilobe catalysts, were investigated experimentally and numerically. The pressure drop and liquid holdup were measured at different gas and liquid velocities and in two different loading methods, namely, sock and dense catalyst loading. The effect of sharp corners on hydrodynamic parameters was considered in a bed with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…Despite a slight over‐prediction, the simulation results showed that the traditional Eulerian multifluid model was able to capture the dynamic pattern of the measured liquid holdup in the case of vertical packed bed (Figures a, a). In line with these results, applicability of the implemented CFD model for the prediction of hydrodynamic behavior of packed beds operating under steady and unsteady state conditions has been demonstrated in some previous studies . Conversely, Figure b revealed an erratic behavior in the model results of the liquid holdup waves for the 15°‐inclined bed.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Despite a slight over‐prediction, the simulation results showed that the traditional Eulerian multifluid model was able to capture the dynamic pattern of the measured liquid holdup in the case of vertical packed bed (Figures a, a). In line with these results, applicability of the implemented CFD model for the prediction of hydrodynamic behavior of packed beds operating under steady and unsteady state conditions has been demonstrated in some previous studies . Conversely, Figure b revealed an erratic behavior in the model results of the liquid holdup waves for the 15°‐inclined bed.…”
Section: Resultssupporting
confidence: 85%
“…Several researchers successfully applied the Eulerian multifluid CFD model along with well‐established interphase interaction forces as closure laws to predict bed overall pressure drop and liquid holdup in conventional vertical gas‐liquid cocurrent downflow packed beds (i.e., trickle‐bed reactors) under steady‐state (i.e., iso‐flow) and unsteady‐state cyclic operation . Hamidipour et al were able to precisely capture the transient hydrodynamic behaviors of trickle‐bed reactors under gas, liquid, and gas/liquid alternating cyclic operations using an unsteady multifluid Euler framework combined with the closure laws developed by Attou et al for fluid‐solid drag forces and fluid‐fluid interaction force.…”
Section: Introductionmentioning
confidence: 99%
“…cylinders and trilobes) can be treated only with cumbersome strategies. This is particularly important because these exotic shapes, such as trilobes, are becoming more and more popular [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Other interesting alternatives are based on the use of Monte Carlo methods [41][42][43] that solve some of the above mentioned issues.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity distributions revealed that liquid hold up and pressure drop are decreased at sharp corners due to the increased void fraction, influenced by the reactor boundaries. 12 In an experimental study, 13 the hydrodynamic aspects of a TBR filled with paper or ceramic bead catalysts were studied through residence time distribution. The paper composite exhibited a better wettability and internal diffusion for the liquid reactants, compared to the ceramic beads, which is in favor of heterogeneous flow.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the decrease in the gas flow rate appreciably increased the residence time . Salimi et al studied the effects of tortuosity and fluid volume fractions on the performance of TBR. The hydrodynamic behaviors of a TBR filled with industrial trilobe catalysts were investigated for two different catalyst loadings through conducting the experiments and CFD modeling.…”
Section: Introductionmentioning
confidence: 99%